Bhagabat Gita in Today’s Mental Therapy practices - Pardhe, Ganesh (Journal of Rapti Babai Campus, 2025)
The Bhagavad Gita is a core concept in Hindu philosophical teachings through which the subconscious mind is able to explain its activities on human change & mental equilibrium. The Gita is a source of practical relief for confused personalities as faith, meditation, and Karma Yoga teach multiple presenting problems to be eased. The current article shows how the teachings of the Gita coincide with recent approaches to psychoanalysis, CBT, and mindfulness-based routines. Faith is thought of as a way to use the transforming effects of belief to cross-refer the subconscious homework we are based on to the higher consciousness; then through meditation, one tries to move to higher consciousness, where noxious patterns of thought no longer exist. To reiterate, conducting Karma Yoga equates to so-called self-donation, which has the potential to raise clarity and evoke intrinsic motivation. It has been accomplished by relying on thematic analysis of the Gita and psychological research which is in the modern era so as to clarify its therapeutic importance in relation to mental health. Consequently, its principles are in alignment with current cognitive restructuring, mindfulness, and intrinsic motivation theories, hence, they are of its offering a proof less explanation to suffer from anxiety, stress, and emotional instability over time. This amalgamation is a bond that Gita’s had that can be put on a pedestal as a respected resource and also mankind’s mental health practice.